2018
DOI: 10.1051/e3sconf/20186202011
|View full text |Cite
|
Sign up to set email alerts
|

The Lorenz system and its generalizations as dynamo models with memory

Abstract: The one of the known applications of the classical Lorenz system is an axisymmetric αω-dynamo with a dynamical quenching of the α-effect by the helicity. In this paper we consider generalizations of the Lorentz system, which are the models of α2 - and α2ω-dynamo. The cases of finite and infinite memory in the quenching functional are considered. The conditions for the existence of stationary dynamo regimes and regimes of regular and chaotic inversions are analytically and numerically studded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The paper analyzes the previously proposed by the author model of a two-mode dynamo [6] from the point of view of the theory of oscillators with hereditary potential. It is shown that with the help of a qualitative analysis of the oscillator, it is possible to establish what…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The paper analyzes the previously proposed by the author model of a two-mode dynamo [6] from the point of view of the theory of oscillators with hereditary potential. It is shown that with the help of a qualitative analysis of the oscillator, it is possible to establish what…”
Section: Resultsmentioning
confidence: 99%
“…The simplest two-mode model of temporal variations of an axisymmetric magnetic field can be written in the following dimensionless form [6]:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A rigorous mathematical derivation of the model is carried out. The general idea of building such a model was previously described in the work of the author [33]. 2.…”
Section: Discussionmentioning
confidence: 99%